Archaeologists : explorers of the human past - Fagan, Brian M. (Oxford profiles., 2003)
Includes eccentric professors and adventuring fortune hunters of old and highly trained scientists of today, Archaeologists collects together biographies of more than 30 archaeologists of the past two centuries. In the process, Archaeologists presents an engaging portrait of how digging for treasure evolved into the respected and vital science we know today.